2016
DOI: 10.4238/gmr15048813
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between gene polymorphisms of CYP1A1, GSTP1, ERCC2, XRCC1, and XRCC3 and susceptibility to lung cancer

Abstract: ABSTRACT. Lung cancer is a common malignant tumor that is characterized by high morbidity and poor prognosis. Studies suggest that an individual's genetic background affects the risk of developing lung cancer. Therefore, we investigated the relationship between gene polymorphisms and susceptibility to lung cancer. We recruited 308 primary lung cancer patients as subjects and 253 healthy adults as controls. After extraction of DNA from blood samples, gene polymorphisms in CYP1A1, GSTP1, ERCC2, XRCC1, and XRCC3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The SNP rs1048943 of CYP1A1 was found to be associated with lung cancer in East Asians [Liu et al, ], which shows colinearity of our finding on Indian population to that of East Asian population. The CYP1A1 (Cytochrome P450; 15q22–24) gene encodes a key phase I endoplasmic and cytosolic xenobiotic metabolism enzyme, present in lung tissue.…”
Section: Discussionmentioning
confidence: 53%
“…The SNP rs1048943 of CYP1A1 was found to be associated with lung cancer in East Asians [Liu et al, ], which shows colinearity of our finding on Indian population to that of East Asian population. The CYP1A1 (Cytochrome P450; 15q22–24) gene encodes a key phase I endoplasmic and cytosolic xenobiotic metabolism enzyme, present in lung tissue.…”
Section: Discussionmentioning
confidence: 53%
“…Variation in expression of XRCC3 has been reported in various cancers, like gastric, breast, lung, skin and colorectal. [18][19][20][21] The most common polymorphism in XRCC3 p.Thr241Met in exon 7 can influence the ability to repair DNA. 21 Allelic variants of XRCC1, XRCC2, and XRCC3 are associated with risk of different types of cancer among different populations all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] The most common polymorphism in XRCC3 p.Thr241Met in exon 7 can influence the ability to repair DNA. 21 Allelic variants of XRCC1, XRCC2, and XRCC3 are associated with risk of different types of cancer among different populations all over the world. [22][23][24] In the world's second-most populous country India, the large and diverse ethnic subpopulations 25 need to be studied to understand the genetic basis of several region-specific complex disorders.…”
Section: Introductionmentioning
confidence: 99%
“…BER pathway gene polymorphisms were reported to be related to the oncogenesis [ 21 23 ]. Recent studies also showed that the mutation of BER pathway genes could increase the radiosensivity by reducing the DNA repair ability [ 24 ].…”
Section: Discussionmentioning
confidence: 99%